Citation Analysis of Undergraduate Projects Report in the Department of Library and Information Science Kabale University Uganda: An In-Text Citation Study - Iroroeavwo Edwin, Achugbue; Benjamin, Ahimbisibwe; Olivia Nina, Rugambwa; Patrick, Odong (Journal of Library and Information Sciences, 2020)
Purpose – The study focused on citation analysis of in-text citations of undergraduate projects research in the department of library and information science, Kabale University Uganda. The purpose is to determine numbers of in-text citations, in-text citations sources, number of in-text citations per programme and students conformity with American Psychological Association style of citations and references. Design/method/approach - The study adopted a citation analysis method to study the in-text citations of undergraduate research projects submitted by graduates of the department of library and information science Kabale University, Uganda. The study covered the period of 2015 to 2019 sets of graduate’s research projects submitted to the department. Analysis focused on in- text citations, in-text citations per programme, in-text citations conformity with APA and in-text citations not in conformity with APA. Findings - The study found that students had the highest number of in-text citations in their research project in 2019 and most of their citations were in journals and books. The study also revealed that programmes in the department of library and information science (Bachelor of Library and Information Sciences- BLIS and Bachelor of Records Management -BRIM)) students’ projects research had the highest number of in-text citations in their research and that most of their in-text citations in both programmes did not conform to APA style of citations. Originality - Undergraduate students of the department of library and information science of Kabale University, Uganda, need good orientation on broad research culture. Most especially in-text citation and referencing this will help them to guild against plagiarism and ensure that sources of research information, authors and literature are acknowledged.